Unusual Multifocal Glomeruloid Pattern in a Well-Differentiated Papillary Mesothelioma of the Peritoneum - Martínez-Consuegra, Nayeli; Muñoz-Juárez, Manuel; Ortíz Hidalgo, Carlos Federico (My University, 2008)
A 46-year-old woman presented to the ABC Medical Center in Mexico City with the clinical picture of acute cholecystitis and underwent cholecystectomy. The patient had no history with regard of asbestos exposure. During surgery, incidental multifocal small firm, white to tan peritoneal nodules were found, ranging from 5 mm to 1 cm, and on frozen section, a diagnosis of papillary epithelial neoplasm consistent with well-differentiated papillary mesothelioma (WDPM) was rendered (Figure 1A). The patient underwent total hysterectomy, along with omentectomy and resection of multiple peritoneal and diaphragmatic implants. The serosal membranes of the uterus and ovary were unremarkable, although a microscopic focus (1 mm) of parenchymal infiltration was found in the left ovary. © International Journal of Surgical Pathology Volume 16 Number 4